Situation at market of steel wire cord and adequacy of reactions of RUP “Belarussian metallurgical works” - V. V. Filippov; S. A. Isakov; V. Ja Genin (Литьë и металлургия)
The situation of metal cord market is analyzed and the necessity of reconstruction of hardware production RUP Belarussian metallurgical works is proved.